Scaling up Sustainable Agriculture Land Management in Bungoma County, Kenya - Shames, Seth; Heiner, Krista; Kapukha, Martha; Wekesa, Amos; Recha, John W.M. (2015)
Agricultural landscapes must provide food, fiber and energy to a growing population in a changing climate, while potentially serving as instruments for climate change mitigation. Agriculture is the backbone of the Kenyan economy, contributing approximately 25% of the GDP annually and employing more than 75% of the population (The Government of Kenya 2010). The development of agriculture is also important for poverty reduction since most of the vulnerable groups, like pastoralists, the landless, and subsistence farmers, depend on agriculture as their main source of livelihoods. Growth in the sector is therefore expected to have a greater impact on a larger section of the population than any other sector. This is especially true in Bungoma County in western Kenya, where the agriculture sector is projected to provide up to 70 percent of jobs between 2013 and 2017 (The County Government of Bungoma 2013).However, climate change presents many challenges, as well as new opportunities, for the development of agriculture, and Bungoma County needs to promote and support sustainable agricultural practices that will improve agricultural productivity, as well as help farmers adapt to and mitigate climate change, at both small and large scale, as outlined in the Bungoma County Integrated Development Plan (CIDP) 2013-2017. This brief provides a review of the potential benefits of Sustainable Agriculture Land Management (SALM) practices, the relevant policy context for implementing them in Bungoma County and suggests policy steps that could be taken by the County government to scale them up.